1995
DOI: 10.1007/bf00223899
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of two genes for resistance to soybean mosaic virus in PI486355 soybean

Abstract: Soybean [Glycine max (L.) Merr.] PI486355 is resistant to all the identified strains of soybean mosaic virus (SMV) and possesses two independently inherited resistance genes. To characterize the two genes, PI486355 was crossed with the susceptible cultivars 'Lee 68' and 'Essex' and with cultivars 'Ogden' and 'Marshall', which are resistant to SMV-G1 but systemically necrotic to SMV-G7. The F2 populations and F2∶3 progenies from these crosses were inoculated with SMV-G7 in the greenhouse. The two resistance gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
100
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 21 publications
4
100
1
Order By: Relevance
“…Of these, resistance derived from Rsv1 and Rsv3 is effective against strains G1-G6 and G5-G7, respectively (Gunduz et al, 2002). Rsv4 was initially thought to provide resistance against all North American strains of SMV but was later shown to exhibit a late susceptible phenotype to strains G1 and G2 (Chen et al, 1993;Ma et al, 1995;Ma et al, 2002;Gunduz et al, 2004). Although none of the Rsv genes have been cloned, some downstream signaling components that regulate Rsv-derived resistance have been identified (Fu et al, 2009;Zhang et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%
“…Of these, resistance derived from Rsv1 and Rsv3 is effective against strains G1-G6 and G5-G7, respectively (Gunduz et al, 2002). Rsv4 was initially thought to provide resistance against all North American strains of SMV but was later shown to exhibit a late susceptible phenotype to strains G1 and G2 (Chen et al, 1993;Ma et al, 1995;Ma et al, 2002;Gunduz et al, 2004). Although none of the Rsv genes have been cloned, some downstream signaling components that regulate Rsv-derived resistance have been identified (Fu et al, 2009;Zhang et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%
“…It was initially named Rsv and found in PI96983 soybean (Kiihl and Hartwig, 1979) and later renamed Rsv1 (Chen et al, 1991). Subsequent studies on soybean cultivars resistant to SMV revealed additional eight different Rsv1 alleles, from cultivars Ogden, York, Marshall, Kwanggyo, 'Raiden', 'Suweon 97', LR1 and PI507389, respectively (Kiihl and Hartwig, 1979;Buss et al, 1997;Buzzell and Tu, 1989;Chen et al, 1991Chen et al, , 1993Chen et al, , 1994Chen et al, , 2001Chen et al, , 2002Ma et al, 1995;Zheng et al, 2005). The responses of soybeans carrying these Rsv1 alleles to different SMV strains are diverse, ranging from extreme resistance and necrosis to mosaic symptoms.…”
Section: Smv-host Interactionsmentioning
confidence: 99%
“…Columbia was also found to carry Rsv4 (in addition to Rsv3) (Ma et al, 2002). Rsv4 is dominant, non-necrotic and non-strain specific, conferring resistance to all strains of SMV (Ma et al, 1995). It was mapped to the molecular linkage group D1b (soybean chromosome 2) where no other resistance genes have been found (Hayes et al, 2000;Saghai Maroof et al, 2010).…”
Section: Smv-host Interactionsmentioning
confidence: 99%
“…In contrast, the Rsv3 gene confers resistance to the G5 to G7 strains of SMV, whereas mosaic or stem-tip necrosis is observed after inoculation of plants with lower-numbered strains of SMV. The Rsv4 gene was initially reported as two independent resistance genes in PI 486355 (Ma et al 1995); this soybean cultivar was later shown to contain the Rsv1 and Rsv4 genes (Buss et al 1997;Hayes et al 2000). Resistance conditioned by genes at the Rsv4 locus has been reported in PI 486355, Peking, and PI 88788 (Ma et al 1995;Gunduz et al 2004).…”
mentioning
confidence: 97%
“…Subsequently, the nine alleles Rsv1-t, Rsv1-y, Rsv1-m, Rsv1-k, Rsv1-r, Rsv1-h, Rsv1-s, Rsv1-n, and Rsv1-d have been identified in Ogden, York, Marshall, Kwanggyo, Raiden, Suwon 97 (Hwangkeumkong), PI 486355, PI 507389, and FT-10, respectively (Chen et al 1991(Chen et al , 1994(Chen et al , 2001Ma et al 1995Ma et al , 2003Silva et al 2004). All Rsv1 alleles except Rsv1-h, which confers resistance to the G1 to G7 strains of SMV, make soybeans necrotic or susceptible to seven SMV strain groups.…”
mentioning
confidence: 98%